Just Popular Entertainment or Longing for a Posthuman Eden?. The Apocalypse in Margaret Atwood's MaddAddam Trilogy Just Popular Entertainment or Longing for a Posthuman Eden? - Stephanie Bender (Journal for Religion, Film and Media, 2019)
In the context of the ecological crisis, tales of the apocalypse have become a regular feature of the contemporary cultural imaginary, be it in popular feature films, non-fictional texts, or dystopian novels. Margaret Atwood's MaddAddam Trilogy investigates this curious form of entertainment by both employing the template of the apocalypse itself, and reflecting on its cause and effect at the same time. The novels reveal how worlds and their respective compasses of good and evil are constructed through story-telling, and that the apocalypse is also a story which functions either as a moral structuring device or as an anaesthetic for the estranged subjects of late capitalism. Assuming a meta-perspective, the MaddAddam Trilogy engenders ethical reflections on possible futures, incorporating recent philosophical strands like transhumanism and posthumanism.